A Prospective Randomized Control Trial Comparing Proximal Femoral Nail and Sliding Hip Screw in The Management of Trochanteric Fracture of The Femur - Kam, NK; Jain, Ashis; Nepal, P; Singh, Mahi Pal; Das, N (Health Renaissance, 2011)
Introduction: There are various implants designed for fixation of trochanteric fracture which can be extramedullary (Sliding hip screw) and intramedullary (Proximal Femoral Nail). A randomized controlled trial comparing these techniques was conducted at BP Koirala Institute of Health Sciences. Objective: To compare efficacy of proximal femoral nail and sliding hip screw in the management of trochanteric fractures. Methods: Patients in both groups were matched for age (mean 67 years, 50 to 100) and gender. We excluded all pathological fractures, patients presenting at more than one week, multiple fractures or any bone and joint disease interfering with rehabilitation. Results: The amount of blood loss and length of incision were significantly higher in the sliding hip screw group (p < 0.05). The time of union, range of movement and Western Ontario and McMasterUniversity knee scores were comparable at two years. The mean Harris hip score was better in proximal femoral group. Conclusion: The number of patients showing shortening, external malrotation and varus angulation was more in sliding hip screw group. There was one case of wound infection and a single case of breakage of implant in sliding hip screw group. Keywords: fracture trochanter; proximal femoral nail; sliding hip screw DOI: 10.3126/hren.v9i1.4354 Health Renaissance, 2011: Vol.9 No.1:7-11